Knockout of OsWRKY71 impairs Bph15-mediated resistance against brown planthopper in rice - Li, Xiaozun; Zhang, Jian; Shangguan, Xinxin; Yin, Jingjing; Zhu, Lili; Hu, Jie; Du, Bo; Lv, Wentang (Frontiers in Plant Science, 2023)
The Bph15 gene, known for its ability to confer resistance to the brown planthopper (BPH; Nilaparvata lugens Stål), has been extensively employed in rice breeding. However, the molecular mechanism by which Bph15 provides resistance against BPH in rice remains poorly understood. In this study, we reported that the transcription factor OsWRKY71 was highly responsive to BPH infestation and exhibited early-induced expression in Bph15-NIL (near-isogenic line) plants, and OsWRKY71 was localized in the nucleus of rice protoplasts. The knockout of OsWRKY71 in the Bph15-NIL background by CRISPR-Cas9 technology resulted in an impaired Bph15-mediated resistance against BPH. Transcriptome analysis revealed that the transcript profiles responsive to BPH differed between the wrky71 mutant and Bph15-NIL, and the knockout of OsWRKY71 altered the expression of defense genes. Subsequent quantitative RT-PCR analysis identified three genes, namely sesquiterpene synthase OsSTPS2, EXO70 family gene OsEXO70J1, and disease resistance gene RGA2, which might participate in BPH resistance conferred by OsWRKY71 in Bph15-NIL plants. Our investigation demonstrated the pivotal involvement of OsWRKY71 in Bph15-mediated resistance and provided new insights into the rice defense mechanisms against BPH.